Factors influencing work stress among non-executive staff / Raziah Zainal Abidin - Zainal Abidin, Raziah (Faculty of Business and Management, 2019)
This research is conducted to determine the factors that influencing work stress among non-executive staff. The study was conducted by distributing 132 sets of questionnaires, which all of it were being distributed conveniently for the non-executive staff that are working at the headquarters (HQ) of Syarikat Air Melaka Berhad. All the questionnaires were answered by respondent using a printed questionnaire. The distribution of questionnaire by hand were done from 1st until 3rd November 2019 and the time of distribution are starting from 9 am until 4.30 pm. Based on the data finding, it shows that two out of three independent variable which is workload and interpersonal relationship have positive relationship towards work stress. Besides that, the hypothesis that were developed at the beginning stage of research process that is (H1) workload has relationship with work stress, (H2) role conflict has no relationship with work stress and (H3) interpersonal relationship has relationship with work stress are supported as the result.